Effects of bacterial contamination on meat decomposition - Imad Ibrahim Ali Al-Sultan; Jasni Sabri (2015)
Microorganisms, mainly bacteria are playing a major role in meat decomposition. The consumption of such microorganisms’ posses’ public health hazard and challenges to related expertise. Among the bacteria that had been isolated from decomposed meat are Pseudomonas fluorescence and Proteus mirabilis as well as zonootic pathogens such as Salmonella typhimurium and Staphylococcus aureus. The growth and survivability of meat contaminants depends on the virulence of the microorganisms and the microenvironment (hydrogen, humidity, oxidation-reduction process, temperatures) that support their metabolism and growth. A room temperature of 20- 25o c has been shown conducive for bacterial growth unlike a cooling temperature of 8 degrees. Studies have shown the penetration of Staph. aureus through the surface of meat depends on the virulence factor of the bacterium and the environment where the meat is stored. Certain bacteria like S. typhimurium and Staph. aureus have the potential to invade more than other bacteria. Researchers in this field did not indicate any consequential discrepancies in the penetration process between lamb and beef meat with the type of bacterium involve in the penetration process. However, fat present in meat either lamb or beef is a natural barrier to penetration into meat which slowdown the penetration process of bacteria. This paper provides an overview of the contamination of meat by pathogens that penetrate and promote decomposition and spoilage of meat and thus affecting quality.